Clinical outcomes of atrial fibrillation screening: a meta-analysis of randomized controlled trials - Langén, Ville; Winstén, Aleksi K.; Airaksinen, K. E. Juhani; Teppo, Konsta (Informa UK Limited, 2025)
Background: Several randomized controlled trials (RCTs) have investigated the benefits of atrial fibrillation (AF) screening. However, since none have shown a significant reduction in stroke rates, the impact of screening on clinical outcomes remains uncertain.
Materials and methods: We conducted a systematic review and meta-analysis of RCTs reporting clinical outcomes of systematic AF screening in participants without known AF. Pooled risk ratios (RRs) were computed for all-cause stroke or systemic embolism, major bleeding, and all-cause mortality, comparing screening with no screening.
Results: Seven RCTs encompassing 76 458 participants were identified. One trial utilized implantable loop recorders for rhythm monitoring, while the others employed non-invasive screening methods. Pooled results indicated that AF screening was associated with a significant reduction in all-cause stroke or systemic embolism (RR 0.932, 95% CI 0.873-0.996, I2 = 0%, p = 0.037), but had no effect on major bleeding (RR 0.996, 95% CI 0.935-1.060, I2 = 0%, p = 0.876) or all-cause mortality (RR 0.987, 95% CI 0.945-1.031, I2 = 0%, p = 0.550). We estimated a number needed to screen of 148 to prevent one stroke or systemic embolism over a 10-year period in a population of 75-year-olds. When only non-invasive screening methods were considered, the reduction in strokes was not statistically significant (RR 0.942, 95% CI 0.880-1.008, I2 = 0%, p = 0.083).
Conclusions: Systematic AF screening is associated with a modest yet statistically significant 7% relative reduction in stroke and systemic embolism, with no observed impact on major bleeding or all-cause mortality.